Features of proximal and distal excitatory synaptic inputs to layer V neurons of the rat medial entorhinal cortex - Medinilla, Virginia (Blackwell Science Inc, 2013)
The entorhinal cortex (EC) has a fundamental function in transferring information between the hippocampus and the neocortex. EC layer V principal neurons are the main recipients of the hippocampal output and send processed information to the neocortex, likely playing an important role in memory processing and consolidation. Most of these neurons have apical dendrites that extend to the superficial layers and are rich in spines, which could be the targets of excitatory inputs from fibres innervating that region. We have used electrical stimulation of afferent fibres coupled with whole-cell patch-clamp somatic recordings to study the features of distal excitatory inputs and compare them with those of proximal ones. The amplitude of putative unitary excitatory responses was ∼1.5 times larger for distal compared with proximal inputs. The responses were purely glutamatergic, as they were abolished by a combination of AMPA and NMDA glutamatergic receptor antagonists. Blockade of I(h) by 4-ethylphenylamino-1,2-dimethyl-6-methylaminopyrimidinium chloride (ZD7288) increased temporal summation; the increase was comparable for proximal and distal inputs. Proximal inputs initiated a somatic spike more reliably than distal ones; in some instances, somatic action potentials triggered by distal stimulation were preceded by dendritic spikes that fully propagated to the soma. Altogether, our results show that medial layer V entorhinal neurons receive excitatory synapses at distal dendritic locations, which gives them access to information encoded by inputs to the superficial layers as well as the deep layers. These findings are fundamentally relevant to understanding the role of the EC in the formation and consolidation of episodic memory.